Handbook of effective inclusive schools research and practice - McLeskey, James 1949-; Waldron, Nancy L.; Spooner, Fred; Algozzine, Bob (Routledge, 2014)
"Over the last decade, the educational context for students with disabilities has significantly changed primarily as a result of mandates contained in NCLB and IDEA. The purpose of this book is to summarize the research literature regarding how students might be provided classrooms and schools that are both inclusive and effective. Inclusive schools are defined as places where students with disabilities are valued and active participants in academic and social activities and are given supports that help them succeed. Effectiveness is addressed within the current movement toward multi-tiered systems of support and evidence-based practices that meet the demands of high-stakes accountability"--Publisher.